Football and reputation management: the role of online communication platforms - Salgado, Paulo Jorge Castro Faria (2011)
Football clubs, as any type of organization, have a reputation to be managed. More than a sport, football is a business activity that generates high revenues, attracts considerable investments and extreme media exposure. Therefore, reputation management might be considered a key function, when it comes to shape the perceptions of a club’s constituents. As Fombrun (1996) noted, reputations are partly a reflection of the organization’s identity and also their efforts to develop a favorable image for themselves. For Argenti (1998), the first role of corporate communication is to establish how a firm wants to be perceived by different constituencies and how it chooses to identify itself. Following this point of view, reputation management lies within the corporate communication function. Nevertheless, as Resnick (2004) states, managing organizational reputation seems to be a difficult or neglected task for most executive managers. For Argenti and Barnes (2009) in the last decade the business of managing relationships has changed and, consequently, the business reality also changed. However, the opposite is also true, the transformations of the business reality have altered the relationships between organizations and its key constituents. Both authors take as fact the existence of a “stakeholder empowerment”, a scenario within which top executives lose authority that is transferred to the organization’s once-passive audiences, such as employees, consumers, media and investors. The rise of the internet and online communications platforms, like social media - or in other words, the development of a web 2.0 model - sponsored the ability of stakeholders to communicate with one another, to build communities, to disseminate their own messages and the possibility to “talk-back”. For Argenti and Barnes (2009) managers have to redefine their strategies and adapt the corporate communication function to this new paradigm. If we take this trends as certain and bring the model to the sports context, than football clubs’ everyday life can be changing radically. Especially because it’s simultaneously a sport activity and a business that tends to generate strong emotional responses from their constituencies that seem to be more than willing to “talk-back”. In order to understand more deeply the surfacing of a “stakeholder empowerment”, the role of online communication platforms and the significance given to reputation management, we have conducted a multiple case study research (Eisenhardt, 1989) within the football context. We studied the 16 Portuguese football clubs that are competing in the first division league in the season 2010/11. With this work we also expect to reveal some clues for future research that might lead to the development of an adequate framework analysis for reputation in football clubs.